Study on the Dehydration Characteristics of Spring Maize after Physiological Maturity and the Suitable Period of Mechanical Grain Harvest. (20th April 2022) - Liu, Guohong; Bian, Qingyong; Fu, Yanbo; Liu, Yanyan; Wei, Yayuan; Zhu, Jinquan; Wang, Zhiguo
Abstract : The high moisture content of seeds during harvesting results in a large amount of grain that breaks during mechanical harvesting, which becomes a key problem that hampers the promotion of mechanical grain harvesting technology. Maize in southern Xinjiang physiologically matures from early September to early October. In this study, 52 varieties of maize at different maturity stages were studied in 2019-2020 and were categorized in the order of physiological maturity time: early September (PD1), mid-September (PD2), late September (PD3), and early October (PD4). The goal of this study was to analyze the differences in content of kernel moisture at physiological maturity and the rate of dehydration after physiological maturity of varieties at different stages of maturity, so as to determine the suitable period for mechanical grain harvesting of maize at different stages of maturity. The results showed that the content of seed moisture at different maturity stages varied in a two-stage linear model, with periods of fast and slow dehydration. An analysis of variance (ANOVA) showed that the content of seed moisture at different stages of physiological maturity did not differ significantly (P > 0.05 ).